2020
DOI: 10.1159/000508764
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Severity of Overactive Bladder Symptoms with Female Sexual Dysfunction and Sexual Satisfaction of Partners

Abstract: <b><i>Purpose:</i></b> Sexual dysfunction in women with overactive bladder (OAB) syndrome has been an important topic, while the sexual satisfaction of partners has not been fully investigated. Our aim was to explore the association between the severity of OAB with female sexual dysfunction and sexual satisfaction of partners. <b><i>Methods:</i></b> A total of 323 patients with OAB recruited in our hospital were included in our study from September 2017 to March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The study results should be interpreted with the following limitations in mind. Presently, the impact of age and BMI on urine levels of choline and acetylcholine, both of which are associated with OAB, is not well understood [ 33 , 34 ]. Though we accounted for differences in age with matching,, in this analysis there were significant differences in BMI between controls and patients with UUI and responders and non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…The study results should be interpreted with the following limitations in mind. Presently, the impact of age and BMI on urine levels of choline and acetylcholine, both of which are associated with OAB, is not well understood [ 33 , 34 ]. Though we accounted for differences in age with matching,, in this analysis there were significant differences in BMI between controls and patients with UUI and responders and non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most women, especially those who already experience OAB symptoms, seldom express concerns about the decline in sexual function. It has been shown that patients with OAB score lower on the Female Sexual Function Index and Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire [ 108 ], indicating that their sexual function is impaired. Traditional pelvic floor physical therapy, anticholinergic medications, and onabotulinumtoxinA (commonly known as Botox) intravesical injections are the first line of treatment for OAB.…”
Section: Pelvic Floor Disordersmentioning
confidence: 99%
“…Possibly, the decrease in the urgency UI episodes with the treatment could also improve these more global aspects of the sexual life. In relation to this, Wang et al [32] performed a study including 323 women with overactive bladder and demonstrated the effect of the severity of its symptoms on the rate of female sexual dysfunction and partners' sexual satisfaction. When the different domains of the overactive bladder were analyzed, the urgency symptoms showed a significant effect on the female sexual function, as more severity of urgency UI has been associated with a higher rate of female sexual dysfunction [32].…”
Section: Urgency Urinary Incontinence Treatment and Sexualitymentioning
confidence: 99%
“…When the different domains of the overactive bladder were analyzed, the urgency symptoms showed a significant effect on the female sexual function, as more severity of urgency UI has been associated with a higher rate of female sexual dysfunction [32]. In this way, UI was closely associated with partners' sexual satisfaction [32]. Serati et al [17] reported that the form of coital UI during orgasm is curable by antimuscarinic treatment in about 60% of cases when associated with detrusor overactivity.…”
Section: Urgency Urinary Incontinence Treatment and Sexualitymentioning
confidence: 99%